The effect of mechanical and thermal treatment on the characteristics of saponite-containing material - Tatyana N. Orekhova; Mariana N. Sivalneva; Mariya A. Frolova; Valeriya V. Strokova; Diana O. Bondarenko (Записки Горного института)
Solving the problems of modern building materials science is reduced to obtaining high-quality materials, expanding and searching for a rational raw material base, which can be carried out through the use of various industrial wastes. In this paper, the possibility of using waste from the mining industry – saponite-containing material (SCM) obtained during the enrichment of kimberlite ores from the Lomonosov diamond deposit, as an active mineral additive for cement binders and concretes is considered. The influence of mechanical and thermal treatment on a number of properties of the material selected from the tailings dump and in its initial state was studied. The study of the surface activity of SCM samples consisted in determining the sorption capacity, acid-base centers and their distribution. An increase in the activity of the surface of the material particles as a result of mechanical activation and its decrease during temperature treatment were determined. These effects are associated with phase rearrangements and structural changes in the sandy-clay rock, which was confirmed during thermal analysis. The temperature effect has no pronounced effect on the microstructure, the “smoothness” of the particles and the formation of a consolidated surface of the structural elements of the saponite-containing material are noted.